Enacting cultural literacy as a dialogic social practice: the role of provisional language in classroom talk. (12th January 2022) - Cook, Victoria; Maine, Fiona; Čermáková, Anna
Abstract : The concept of cultural literacy as a dialogic social practice celebrates alternative perspectives. Navigating multiple perspectives in dialogue requires high 'tolerance of ambiguity' characterised by a positive, open and flexible attitude towards uncertainty. This article aims to explore how provisional language is used in classroom dialogue to enact tolerance of ambiguity and its associated democratic behaviours. It draws on data collected as part of a larger European-funded project in which children and young people used wordless texts as springboards to engage in discussions about cultural themes. We report findings from an in-depth qualitative analysis of two lessons (for 9–10-year-olds and 13–14-year-olds) chosen due to their use of provisional language and focus on multiple perspectives. We explore how the social element of provisional language enables students to enact key democratic behaviours as they learn to navigate multiple perspectives in small peer-group learning contexts. We find that teacher modelling and dual objectives in promoting such language are central to creating a safe dialogic space with inherent democratic potential that is not bound by solution-seeking goals. We consider the pedagogical implications of this by problematising the role of dialogue in enacting democratic behaviours through a critical exploration of the concept of 'voice'.